Wearable Electrical Impedance Tomography Belt With Dry Electrodes - Lin, Bor-Shing; Yu, Hong-Ren; Kuo, Yu-Ting; Liu, Yu-Wei; Chen, Heng-Yin; Lin, Bor-Shyh (IEEE transactions on biomedical engineering, 2022)
Objective: Electrical impedance tomography (EIT) is a noninvasive imaging technology used to reconstruct the conductivity distribution in objects and the human body. Methods: In recent years, numerous EIT systems and image reconstruction algorithms have been developed. However, most of these EIT systems require conventional electrodes with conductive gels (wet electrodes) and cannot be adapted to different body types, resulting in limited applicability. Results: In this study, a wearable wireless EIT belt with dry electrodes was designed to enable EIT imaging of the human body without using wet electrodes. The specific design of the belt mechanism and dry electrodes provide the advantages of easy wear and adaptation to different body sizes. Additionally, the Gauss-Newton method was used to optimize the EIT image. Conclusion: Finally, experiments were performed on the phantom and human body to validate the performance of the proposed EIT belt. Significance: The results demonstrate that the proposed system can provide accurate location information of the objects in the EIT image and the system can be successfully applied for noninvasive measurement of the human body.